A Tinjauan Desain Formulir Assesment Diruang Saraf Di RSU Syifa Medika Banjarbaru Tahun 2019 - Ni wayan Kurnia Widya Wati; Ermas Estiyana; Rezki Abdillah (HB PRESS, 2019)
Syifa Medika Banjarbaru General Hospital has not yet used an assesment form for the nerv room in hospitalization. Due to the absence of a medical record committee who design the patient assessment form. The purpose of an assessment form design in inpatients nerve room is to support the the accreditation and data completeness data and at Syifa Medika Banjarbaru General Hospital. This research uses a descriptive methode with 4 respondents consist of doctors, nurses, and heads of medical records. Based on the results of this research conducted by interviewing neurologist, head nurse, chairman room nurse coordinator, and head of medical records. The conclusions of this research are aspects that exist in the inpatient assessment form at the nerve room, namely physical aspects, anatomical aspects, and content aspects, designing nerve assessment forms and medical nursing assessments for Syifa Medika General Hospital Banjarbaru.